DISTRIBUSI PENDAPATAN PETANI CENGKIH DI DESA TANGKUNEI KECAMATAN TUMPAAN KABUPATEN MINAHASA SELATAN - Marlina M. Posumah; Mex L.F. Sondakh; Eyverson Ruauw (Jurusan Sosial Ekonomi Pertanian, Fakultas Pertanian Universitas Sam Ratulangi, Manado, 2019)
The purpose of this study was to analyze the income distribution of clove farmers in Tangkunei Village. The data used in this study were primary and secondary data. Primary data were obtained through direct interviews using questionnaires. Respondents were selected using Simple Random Sampling Method. Secondary data were obtained through relevant agencies such as the Tangkunei Village Office, online media, and journals. The data analysis used in this study was descriptive data analysis, namely by using the Gini Index, Lorenz Curve and World Bank Criteria.The results of this study indicated that the level of inequality of farmer income from Clove farming alone could be classified as having a moderate inequality (Gini Index of 0.39). If the income outside of clove farming was taken into account,Â the level of inequality would decrease as indicated by the Gini Index of 0.31.Keywords: Income Distribution, Clove Farmers. Tumpaan Village